2011
DOI: 10.1007/s00417-011-1837-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term corneal endothelial cell changes in pediatric intraocular lens reposition and exchange cases

Abstract: The density of corneal endothelial cells was conspicuously decreased after IOL reposition or exchange procedures in childhood cases. Longer follow-up must be conducted in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
2
1
Order By: Relevance
“…Severe endothelial cell loss and morphologic changes were seen in patients who received AC IOLs compared with PC IOLs, 23 and the density of corneal endothelial cells conspicuously decreased after IOL repositioning or exchange procedures, although there was no significant difference in the decrease between the two groups. 33 In our study, the mean percentage change in endothelial cell density from preoperatively to postoperatively decreased significantly, by 5.09% in IOL refixation and 5.93% in IOL exchange, but there was no significant difference between the two groups. Nd : YAG capsulotomy can be a trigger factor by weakening the zonules, in addition to their effect on the capsule.…”
Section: Discussioncontrasting
confidence: 49%
“…Severe endothelial cell loss and morphologic changes were seen in patients who received AC IOLs compared with PC IOLs, 23 and the density of corneal endothelial cells conspicuously decreased after IOL repositioning or exchange procedures, although there was no significant difference in the decrease between the two groups. 33 In our study, the mean percentage change in endothelial cell density from preoperatively to postoperatively decreased significantly, by 5.09% in IOL refixation and 5.93% in IOL exchange, but there was no significant difference between the two groups. Nd : YAG capsulotomy can be a trigger factor by weakening the zonules, in addition to their effect on the capsule.…”
Section: Discussioncontrasting
confidence: 49%
“…Surgically induced astigmatism was not evaluated in this study, but postoperative astigmatism was comparable between the groups. Recent retrospective studies reported a significant decrease in corneal ECD after both refixation and exchange of a dislocated IOL, and reported no significant differences in corneal ECD at 6 months after surgery or in the ECD decrease between the groups [19,20,24]. However, ECD change in the present study was remarkably consistent with a prospective randomized trial by Kristianslund et al that compared IOL reposition by scleral suture and exchange with retropupillary fixation of an iris-claw IOL [22].…”
Section: Discussionsupporting
confidence: 90%
“…Notably, the most common postoperative complication was a significant decrease in endothelial cell density in both the IOL exchange and the IOL refixation groups. Wang et al [ 16 ] reported that corneal endothelial cell density decreased remarkably after IOL exchange or refixation surgery without a significant difference in the decrease between the two groups. We initially predicted that the IOL refixation group would have less decrease in endothelial cell density than the IOL exchange group because the smaller incision would cause less trauma to the corneal endothelium.…”
Section: Discussionmentioning
confidence: 99%